The practice of primary school mathematics teachers of blended learning in the educational process in Dawadmi Governorate - Al-Otaibi, Saad Farhan Mohammed (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the degree of practice of blended learning by mathematics teachers in the primary stage, and its requirements in the educational process in Dawadmi Governorate. 225) of the mathematics teachers. The results of the study concluded that the degree of practice for blended learning was very high, and the degree of its requirements in the educational process was very high. The study also revealed that there are statistically significant differences for the average degree of practice in the response of the sample members according to the variable “gender.” “In favor of the female teachers, and there are statistically significant differences for the average practice requirements for the benefit of the teachers, the study also revealed that there are no statistically significant differences between the average response of the sample members according to the variable “Teaching experience.” In light of the results, the study recommended the necessity of providing qualified trainers to train teachers and female teachers On blended learning techniques, providing a guide on how to deal with them, and taking care of preparing and preparing the infrastructure in schools in order to benefit from technology A wireless.